Rotigotine transdermal system: developing continuous dopaminergic delivery to treat Parkinson's disease and restless legs syndrome. (21st August 2014) - Benitez, Arturo; Edens, Heather; Fishman, Jesse; Moran, Kimberly; Asgharnejad, Mahnaz
Abstract : Rotigotine is a nonergoline dopamine receptor agonist with structural similarity to dopamine. Rotigotine binds to the D1 through D5 dopamine receptors, having several times more affinity than dopamine does to the D2 and D3 receptors. Although rotigotine was demonstrated to restore locomotor activity in animal models of Parkinson's disease (PD), the rapid metabolism of rotigotine limited the development of an orally administered formulation. Rotigotine's high lipid solubility and extended duration of action when applied to the skin in experimental models of PD suggested that rotigotine was a candidate for transdermal application. The constant transdermal delivery of rotigotine over 24 h is hypothesized to approximate continuous agonist–receptor stimulation, which conceptually more closely mimics physiologic striatal dopamine receptor function. Randomized clinical studies have demonstrated rotigotine's efficacy, safety, and tolerability in patients with early‐ and advanced‐stage PD, including improvements in motor symptoms and off‐time. Although the etiology is unknown, restless legs syndrome (RLS) is thought to involve dopaminergic dysregulation. Randomized clinical studies also have demonstrated the efficacy of rotigotine in improving the symptoms of moderate‐to‐severe primary RLS. This review examines rotigotine's developmental history for transdermal administration leading to its approval for the treatment of early‐ and advanced‐stage PD and moderate‐to‐severe primary RLS.